The Practice of Violence Cycle in Schools - Rinaldi, Kasmanto; Hermawan, Doni (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Violence within the realm of education is characterized by aggressive behaviors that exceed permissible limits of authority, inevitably resulting in the infringement of victims' rights. One such manifestation is the persistence of a seniority culture, which contributes to diminished self-esteem among students. The prevalence of this culture in educational settings detrimentally impacts children, fostering engagement in deviant behaviors, as evidenced in a case at Vocational High School X in Pekanbaru. Employing a descriptive methodological approach, this research aims to elucidate the dynamics of violent practices perpetrated by students in schools and to identify the underlying factors sustaining this culture of violence. Theoretical frameworks utilized in this study include subcultural theory and differential association theory. This study finds that violence in the educational milieu constitutes aggressive behavior exceeding permissible boundaries of authority, thereby violating victims' rights. The repercussions of such violence can be profound, particularly in terms of its impact on victims' mental well-being. Factors contributing to juvenile delinquency encompass internal factors, familial dynamics, and environmental influences. Violent conduct is often fueled by impulsive inclinations, which rationalize students' involvement in such behaviors. Furthermore, a lack of self-control exacerbates individuals' difficulty in regulating their conduct, thereby blurring distinctions between acceptable and unacceptable behaviors. In this context, the perpetuation of violence can be traced back to familial legacies, perpetuated through successive generations and compounded by external influences.